Protocol, or the "Chivalry of the Object". - Yeager, Stephen M. (Critical Inquiry)
The article explores protocols and their self-historicization. Topics discussed include information on author Alexander Galloway's "Protocol: How Control Exists After Decentralization," tendency noted by author Patrick Jagoda for critical analyses of digital networks, and comparison of protocol to a succinct description of chivalry in poet Geoffrey Chaucer's moral ballad "Gentilesse."